Morphological comparison of tympanal organs between Phycitinae and Pyralinae (Lepidoptera: Pyralidae) - Özyolci̇ Büşra; Çalişkan, Selma Seven (Zootaxa, 2024)
Tympanal organ plays an important role for insects in perception, fleeing from predators, defense, finding and choosing sex, communication, and carrying out social interactions. It is positioned in different areas among various insect groups. Tympanal organ is in the abdomen in the Pyralidae family, many species of which are harmful to economically important agricultural products and storage products. This study was conducted to determine the importance of the tympanal organ in the classification of Pyralids. For this purpose, tympanal organs of 10 species (Pyralis farinalis (Linnaeus, 1758), Hypsopygia glaucinalis (Linnaeus, 1758), Endotrichia flammealis ([Denis & Schiffermüller], 1775), Dioryctria pineae (Staudinger, 1859), D. mendacella (Staudinger, 1859), Oncocera semirubella (Scopoli, 1763), Etiella zinckenella (Treitschke,1832), Acrobasis obliqua (Zeller, 1847), Myelois circumvoluta (Geoffroy in Fourcroy, 1785), Ematheudes punctellus (Treitschke, 1833) in four tribus belonging to Pyralinae and Phycitinae were examined for the first time. Bulla tympani, fornix tympani, pons tympani, rugae odontinae, intersegmental thoraco abdominal membrane, processus spiniforme etc. structures of these species were described and photographed for the first time. The similarities and differences between taxa were analyzed.